2018
DOI: 10.1155/2018/2563293
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Budget and Economic Assessment of Blended Fertilizer Use in Kenya Tea Industry

Abstract: Kenya’s tea industry depends predominantly on imported compound NPK fertilizers to replenish nutrients removed through plucking. These fertilizers cannot be easily manipulated for specific soils and tea clones. They also frequently become hazardous within tea-growing environments. In this respect, two fertilizer blends containing NPKS 25 : 5 : 5 : 4 + 9Ca + 2.62Mg and NPKS 23 : 5 : 5 : 4 + 10Ca + 3Mg with trace elements have been produced commercially in the country. However, the extent to which the blended fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The sole application of mineral fertilizers at different rates in both years were highly profitable (average VCR = 11). Findings in this study are consistent with Dicko et al 2017 andSitienei et al (2018) confirming the high profit potential of applying mineral fertilizers on crops. The implication of these results reiterates the integral role of site-specific nutrients application in sustainable crop production, soil fertility management (Angus et al, 2004;Ogundijo et al, 2015), and overall maximizing the net financial returns of farmers.…”
Section: Economic Appraisalsupporting
confidence: 88%
“…The sole application of mineral fertilizers at different rates in both years were highly profitable (average VCR = 11). Findings in this study are consistent with Dicko et al 2017 andSitienei et al (2018) confirming the high profit potential of applying mineral fertilizers on crops. The implication of these results reiterates the integral role of site-specific nutrients application in sustainable crop production, soil fertility management (Angus et al, 2004;Ogundijo et al, 2015), and overall maximizing the net financial returns of farmers.…”
Section: Economic Appraisalsupporting
confidence: 88%
“…New Mavuno also contained other nutrients, including K, which is taken up in relatively high amounts by root and tuber crops (Koch et al., 2020; Wortmann et al., 2020). Studies have revealed better crop performance with the application of compound fertilizer (Habte & Ayalew, 2017; Sitienei et al., 2018; van Erp et al., 2014). Apart from the immediate effect on the applied fertilizer, maintenance of soil nutrients is crucial for sustainable production (Koch et al., 2020; Schut & Giller, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Site‐specific fertilizer management has been evaluated in recent years through nutrient omission trials to capture the potential presence of limiting nutrients and responses (Kihara et al., 2016; Mugo et al., 2021; Nziguheba et al., 2009). Fertilizer blending is used in Kenya to produce crop‐specific and site‐specific fertilizer (GIZ, 2016; Sitienei et al., 2018), and these fertilizer blends are available in the market. The fertilizers are based on crop nutrient removal as well as the general soil chemical properties of various areas (GIZ, 2016; Kinyua et al., 2013; Mbuthia, 2018; Yara, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other sources of nutrients were wastes from livestock that grazed around groundwater resources as well as using them as watering points. The unabsorbed nutrients were perhaps leached and percolated with gravity rainwater into the shallow groundwater sources and aquifers (Sitienei et al, 2013(Sitienei et al, , 2018.…”
Section: Effects Of Land-use Changes On Groundwater Resources' Physic...mentioning
confidence: 99%